ANALISIS RISIKO PRODUKSI USAHATANI PADI DI PESISIR DANAU TEMPE - Ros Mita; Rahim Darma; Rahmadani Rahmadani; Muslim Salam; A. Amrullah (Hasanuddin University, 2020)
Production risk is an occurrence of uncertainty in the agriculture sector and potentially potential loss and as a deviation from the agricultural production result obtained with the expected. This study aims to (1) To know the risk farming production at the shore of Lake Tempe in Mallusesalo Village, Sabbangparu District, Wajo Regency; and (2) To identify the efforts that need to be made by farmers in mitigating the risk of production of Lake Tempe coastal rice farming in Mallusesalo Village, Sabbangparu District, Wajo Regency. Data analysis techniques used are farm income analysis, coefficient of variation (CV) analysis, and descriptive analysis. The results of this study show that the average income of farmers is in Mallusesalo village of Rp. 17,243,261 / ha per season. Production risk obtained coefficient of variation (CV) of 0.046 can be interpreted as rice farming in Mallusesalo village has a low production risk. Efforts that need to be done by farmers in mitigating production risk are farmers observing weather conditions by referring to the planting calendar by taking into account the time of planting based on climate conditions. If there are signs of pest and disease attacks, farmers should prepare medicines (pesticides) accordingly. In addition, farmers can choose superior rice seed varieties, and farmers can also carry out biological biological control by utilizing natural enemies to reduce pest population.Keyword : Production; Risk; Mitigate; Rice; Lake Tempe